2004
DOI: 10.1038/sj.jea.7500355
|View full text |Cite
|
Sign up to set email alerts
|

Impact of improved stoves, house construction and child location on levels of indoor air pollution exposure in young Guatemalan children

Abstract: The goal of this study was to assess the impact of improved stoves, house ventilation, and child location on levels of indoor air pollution and child exposure in a rural Guatemalan population reliant on wood fuel. The study was a random sample of 204 households with children less than 18 months in a rural village in the western highlands of Guatemala. Socio-economic and household information was obtained by interview and observation. Twentyfour hour carbon monoxide (CO) was used as the primary measure of kitch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
94
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(110 citation statements)
references
References 13 publications
10
94
6
Order By: Relevance
“…The installation of the Patsari stoves resulted in a median 71% reduction in 48-h PM 2.5 concentrations near the stove and 58% reduction in the kitchen; however, indoor concentrations remained nearly four times higher than outdoor standards. Several studies that have been conducted in Guatemala to evaluate the impacts of the plancha stove on indoor air pollution (Naeher et al, 2000;Albalak et al, 2001;Bruce et al, 2004) found comparable results. These studies, however, were longitudinal in design, and therefore the changes in concentrations found could be influenced by household factors (such as household size, income, design, etc.)…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The installation of the Patsari stoves resulted in a median 71% reduction in 48-h PM 2.5 concentrations near the stove and 58% reduction in the kitchen; however, indoor concentrations remained nearly four times higher than outdoor standards. Several studies that have been conducted in Guatemala to evaluate the impacts of the plancha stove on indoor air pollution (Naeher et al, 2000;Albalak et al, 2001;Bruce et al, 2004) found comparable results. These studies, however, were longitudinal in design, and therefore the changes in concentrations found could be influenced by household factors (such as household size, income, design, etc.)…”
Section: Discussionmentioning
confidence: 82%
“…Adaptation to improved Patsari stoves can mean a significant behavioral change for many women, as it often includes shifting from cooking on the floor in a kneeling position to the standing position, chopping wood into smaller pieces, longer cooking times, and technology that requires frequent maintenance for adequate performance. The impact of the stoves on indoor air quality may improve with time, as participants use their stoves more, or deteriorate as participants abandon the new technology or fail to provide proper maintenance or use, as has been observed with other stove dissemination efforts (Bruce et al, 2004). It is important, therefore, that longer term impacts of improved stove programs are also evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on personal exposure to pollutants in biomass smoke are necessary for analysis of association with disease outcomes, but has been measured or estimated in few studies (Ezzati et al, 2000;Naeher et al, 2001;Balakrishnan et al, 2002;Bruce et al, 2004;Dasgupta et al, 2006;Mestl et al, 2007;Dionisio et al, 2008;McCracken et al, 2009). In particular, a metric of usual exposure is desired because exposure may vary from day to day and health effects may depend on cumulative exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Urban drainage improvements and improved household water storage systems can reduce urban malaria [69]. Improved wood stoves (biofuel stoves), substitution of biofuels with gas or other improved rural fuel/energy sources, and improved kitchen ventilation all reduce exposure of women and young children to harmful indoor air pollutants arising from exposure to smoke from traditional woodstoves and open fires [70]. Solar stoves, solar water disinfection and solar energy panels are possible alternatives to traditional wood stoves, boiling water with biofuels and burning kerosene lamps in the home, though their higher costs must be addressed [71].…”
Section: Discussionmentioning
confidence: 99%